Sociodemographic Factors Affecting Household Food Security In Sumedang Regency West Java Province - Nugrahana Fitria Ruhyana; Wiedy Yang Essa; Mardianis Mardianis (AGRARIS: Journal of Agribusiness and Rural Development Research, 2020)
Sumedang Regency is categorized as food security at the regional level based on the 2015 Food Security and Vulnerability Atlas (FSVA), but at the household level, there are still cases of food insecurity. The problem faced is that the determinants of food security have not been identified based on household characteristics. The objective of this study was to determine the sociodemographic factors that affect household food security in Sumedang Regency. This study uses a quantitative method with 690 household analysis units obtained from the 2015 Susenas data. Data were analyzed by the logistic regression method. Sociodemographic factors that affect household food security in Sumedang Regency in 2015 from the aspect of household head characteristics are education, age, and smoking habits. While from the aspect of a household is the number of household members, rural residence, and position in work as a farm laborer. Household food security in Sumedang Regency will be better if there is an increase in household income sources of farm laborers, increased economic activity in rural communities, and expansion of community education accessibility, optimization of family planning programs, and increased knowledge and awareness of healthy living behaviors by reducing smoking habits.